Old wine in new bottles: Tobacco industry's submission to European Commission tobacco product directive public consultation - Hiilamo, Heikki (Health Policy, 2014)
Between September and December 2010 the European Commission Health & Consumer Protection Directorate-General (DGSANCO) held a public consultation on a possible revision of the European Union Tobacco Products Directive (2001/37/EC). We used content analysis of the tobacco industry's and related parties' 300 submissions to the public consultation to determine if tobacco industry and its allies in Europe are prepared to reduce harm of the tobacco products as their public statements assert. The industry submission resorted to traditional tobacco industry arguments where illicit trade and freedom of choice were emphasized and misrepresented the conclusions of a DGSANCO-commissioned scientific report on smokeless tobacco products. Retailers and wholesalers referred to employment and economic growth more often than respondents from other categories. The pattern of responses in the submission differed dramatically from independent public opinion polls of EU citizens' support for tobacco control policies. None of the major tobacco manufacturers or their lobbying organizations supported any of the DGSANCO's proposed evidence based interventions (pictorial health warnings, plain packaging or point-of-sale display bans) to reduce harms caused by cigarette smoking.